Phytochemical Profile and Cervical Anticancer Activity of an In Vitro n-Hexane Extract of Kunto Dewo Fruit (Kigelia pinnata) Peel and Flesh - Isbandiputri, Swarnasari Nurandita; Dwira, Surya; kristanty, diyah (Indonesian Journal of Medical Chemistry and Bioinformatics, 2023)
Cervical cancer is the fourth highest cancer occurring and causes death in women. Therefore, adequate management is needed to prevent its development. Currently, the treatment has a variety of adverse side effects, so it needs alternative treatments that are supportive and with minimal side effects. One way is to use herbal plants, such as the Kunto Dewo (Kigelia pinnata) plant which is often used as traditional medicine. This plant has antimicrobial and cytotoxic effects on cancer cells. Knowing the phytochemical profile and in-vitro anticancer activity of the n-hexane extract of peel and flesh of Kunto Dewo (Kigelia pinnata) fruit against cervical cancer HeLa cells. The peel and flesh of Kigelia pinnata fruit are macerated in n-hexane solvent then the resulting filtrate is evaporated to become an extract. The extract is used for phytochemical profile, carry out through phytochemical screening, thin layer chromatography, calculation of total phenol, and total flavonoids. The extract was also tested for cytotoxic activity against cervical cancer HeLa cells using MTT assay. The n-hexane extract of the peel and flesh of the kigelia pinnta fruit contains triterpenoids. In TLC analysis, there were found 4 components in the n-hexane extract of Kigelia pinnata fruit peel and 8 components in the n-hexane extract of Kigelia pinnata fruit flesh. The cytotoxic activity of the n-hexane extract of the peel and flesh of Kigelia pinnata fruit is included in the moderately active category. The n-hexane extract of the peel and flesh of the kigelia pinnata fruit has potential as an anti-cervical cancer.